2023
DOI: 10.3390/life13020307
|View full text |Cite
|
Sign up to set email alerts
|

Green Biomass-Based Protein for Sustainable Feed and Food Supply: An Overview of Current and Future Prospective

Abstract: It is necessary to develop and deploy novel protein production to allow the establishment of a sustainable supply for both humans and animals, given the ongoing expansion of protein demand to meet the future needs of the increased world population and high living standards. In addition to plant seeds, green biomass from dedicated crops or green agricultural waste is also available as an alternative source to fulfill the protein and nutrient needs of humans and animals. The development of extraction and precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 123 publications
0
9
0
Order By: Relevance
“…The state of the art of green-biomass originated protein in Europe and America as well as the results of an extensive internet search with keywords "plant based foods" and "plant based protein" have been summarized. 88 There is a need for a science-based approach to design healthy and sustainable plant based foods. 89 A roadmap for plant proteins for future foods has been presented, focusing on means to enhance protein functionalities.…”
Section: Food Processing Technologiesmentioning
confidence: 99%
“…The state of the art of green-biomass originated protein in Europe and America as well as the results of an extensive internet search with keywords "plant based foods" and "plant based protein" have been summarized. 88 There is a need for a science-based approach to design healthy and sustainable plant based foods. 89 A roadmap for plant proteins for future foods has been presented, focusing on means to enhance protein functionalities.…”
Section: Food Processing Technologiesmentioning
confidence: 99%
“…Novel sustainable products derived from grass, such as paper and packaging, nanofibers, animal bedding, novel protein feeds, extracted proteins, biochemicals, nutraceuticals, bioactive compounds, biogas and biochar are seen to create new sustainable business opportunities in rural areas [ 5 , 6 ]. The concept of biorefining green biomass is not novel, as pointed out in a recent review by Domokos-Szabolcsy et al [ 7 ], who referred to the extensive work and number of publications by a Hungarian scientist and innovator Károly (Karl) Ereky since 1920’s. The use of protein extracted from green leaves for nutrition of humans and monogastric farm animals was also brought up in UK, motivated by the Second World War [ 8 ] and green crop fractionation was extensively studied in the 1970’s [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, grass silage contains several components such as neutral detergent fibre, crude protein (CP), water soluble carbohydrates, fermentation end products, minerals and bioactive compounds to a variable extent, so that a single component cannot dominate the product portfolio. The number of various phytochemicals in green biomasses is high as demonstrated by the analytical work reported by Domokos-Szabolcsy et al [ 7 ], who listed 46 different compounds identified by UHPLC-ESI-MS analysis. Potentially, extraction of phytochemicals of high added value could be included in a biorefinery operation.…”
Section: Introductionmentioning
confidence: 99%
“…Several promising alternative protein sources for food and feed are suggested in the literature, e.g., insects, algae, and green leafy biomass, the latter is globally available in large quantities in the form of plant leaves. This feedstock contains the protein ribulose-1,5-bisphospate-carboxylase/oxygenase (RuBisCO), which catalyzes carbon fixation in the photosynthetic cycle . Approximately 50% of the proteins in green biomass is RuBisCO and the protein is also the most abundant in the world .…”
Section: Introductionmentioning
confidence: 99%
“…Also, the negative impact of meat production is reduced if protein from green biomass is used as feed, e.g., the climate impact of pork is decreased by 17% when fed grass-clover protein . The concept of using green leafy biomass as a protein source is not new (the history is comprehensively reviewed by Domokos-Szabolcsy et al), but the development of novel technologies and processes, together with an ever more urgent need for alternative protein sources, has resulted in a renewed interest in this protein source…”
Section: Introductionmentioning
confidence: 99%